Implementasi Supervisi Akademik Berbasis Coaching Dalam Meningkatkan Kualitas Pembelajaran Pada Kurikulum Merdeka - Yulidar; Fatqul Hajar Aswad; M. Badrun (Universitas Muhammadiyah Surakarta, 2025)
This study aims to analyze the implementation of coaching-based academic supervision in improving the quality of learning in the Independent Curriculum. Rooted in the theory of academic supervision and coaching, this study highlights the importance of implementing coaching-based academic supervision in the TIRTA (Objectives, Identification, Action Plan, and Responsibilities) flow. The research method used is qualitative with a case study approach, involving observation, in-depth interviews, and document analysis. The findings of the study show that supervision plays an active role in helping teachers through a participatory and holistic approach, involving classroom observation, self-reflection, and constructive feedback. Supervision helps agree on goals, identify teachers’ weaknesses and strengths, develop development action plans that are directed and in accordance with teachers’ needs, significantly improve the quality of learning in line with the TIRTA model. Motivation and support from supervision encourage teachers to develop innovative ideas, while shared commitment and structured monitoring ensure the successful implementation of the action plan. Obstacles in the implementation of supervision can be overcome with an adaptive, empathetic, and continuous training approach. An important contribution of the research is the development of supervision strategies that empower teachers and support the implementation of a student-cantered curriculum. This study suggests the importance of coaching-based academic supervision as an effective approach in supervision in helping teachers support and empower teachers to improve the quality of learning in the Independent Curriculum.